ESG PILLARS AND EARNINGS MANAGEMENT: A SYSTEMATIC LITERATURE REVIEW - Ashiilah Maheswari Widyarto (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2025)
Research on the relationship between ESG and earnings management has grown substantially within the academic community. This trend raises questions about how each ESG pillar (environmental, social, and governance) influences earnings management differently. This systematic literature review aims to analyze the influence of ESG pillars on earnings management. Employing the PRISMA methodology, we identified quantitative research articles published in English and Indonesian between 2018 and 2025. We excluded studies that were not indexed in major databases or did not directly address ESG metrics. Six studies include the ESG pillars as independent variables and earnings management as the dependent variable. This SLR presents how these six studies define ESG pillars and earnings management, specifying the measures and proxies used. Our review reveals that the environmental pillar is positively associated with earnings management, predominantly accrual-based earnings management. In contrast, the governance pillar exhibits a significant negative association, indicating that stronger governance mechanisms restrain opportunistic financial reporting. The social pillar yields mixed results: some studies report a negative relationship, while others report a positive relationship, suggesting further investigation. The review also recommends future research to detail pillar scores and explore ESG sub-pillars. In summary, these findings underscore the contrasting roles that environmental and governance factors play in shaping earnings management decisions by corporate managers.